Sistem Manajemen Inventori Gadget dengan Metode Waterfall - Yamin Nuryamin; Eko Setia Budi; Abdul Rahman Kadafi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Stock management system online can do supervision for the better.Lack of supervision be negative effects for the acceptance or expenditure so management reporting and oversight of the use of goods delayed.The purpose of this research has persediaan management information system in use of terjun mhk gadgets that can be accessed and supervised online.Design system using the unified modelling language, programming language and mysql php database.Research it produces persediaan management information system that provides information goods in and freight out and facilitate report receipts and disbursements goods, so that the be stock the information can be conducted easily.